2022
DOI: 10.1182/blood.2021013925
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 chromatin regulators induce transcriptional networks involved in GATA2 and proliferation during MPN progression

Abstract: Myeloproliferative neoplasms (MPN) transform to myelofibrosis (MF) and highly lethal acute myeloid leukemia (AML), although actionable mechanisms driving progression remain elusive. Here, we elucidate the role of the High Mobility Group A1 (HMGA1) chromatin regulator as a novel driver of MPN progression. HMGA1 is up-regulated in MPN with highest levels after transformation to MF or AML. To define HMGA1 function, we disrupted gene expression via CRISPR/Cas9, short hairpin RNA, or genetic deletion in MPN models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…First, we found that HMGA1 expression (mRNA and protein) is higher in PDAC cell lines derived from metastatic tumors compared with those from primary tumors (65) (Supplemental Figure 1, A-E; supplemental material available online with this article; https://doi.org/10.1172/JCI151601DS1). Next, we silenced HMGA1 via lentiviral delivery of short hairpin RNAs (shRNAs) targeting 2 different sequences (49) in cell lines from primary and metastatic tumors harboring common PDAC mutations: (a) E3LZ10.7 (66), from a liver metastasis with KRAS G12D and homozygous SMAD4 deletion; (b) MIA PaCa-2 (67), from a primary PDAC with homozygous CDKN2A/p16 INK4A deletion, mutant KRAS G12C , and TP53; and (c) AsPC-1 (67), from PDAC ascites fluid with homozygous mutations in KRAS G12D , TP53 C135fs* 35 , and CDKN2A L78fs*41 . Strikingly, HMGA1 deficiency disrupted proliferation, clonogenicity, migration, invasion, and 3-dimensional (3D) sphere formation in all cell lines tested (Figure 1), indicating that HMGA1 is required for these oncogenic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we found that HMGA1 expression (mRNA and protein) is higher in PDAC cell lines derived from metastatic tumors compared with those from primary tumors (65) (Supplemental Figure 1, A-E; supplemental material available online with this article; https://doi.org/10.1172/JCI151601DS1). Next, we silenced HMGA1 via lentiviral delivery of short hairpin RNAs (shRNAs) targeting 2 different sequences (49) in cell lines from primary and metastatic tumors harboring common PDAC mutations: (a) E3LZ10.7 (66), from a liver metastasis with KRAS G12D and homozygous SMAD4 deletion; (b) MIA PaCa-2 (67), from a primary PDAC with homozygous CDKN2A/p16 INK4A deletion, mutant KRAS G12C , and TP53; and (c) AsPC-1 (67), from PDAC ascites fluid with homozygous mutations in KRAS G12D , TP53 C135fs* 35 , and CDKN2A L78fs*41 . Strikingly, HMGA1 deficiency disrupted proliferation, clonogenicity, migration, invasion, and 3-dimensional (3D) sphere formation in all cell lines tested (Figure 1), indicating that HMGA1 is required for these oncogenic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of the gene encoding the chromatin regulator HMGA1 occurs in most aggressive tumors, including PDAC, where high levels portend poor differentiation and adverse outcomes . The HMGA1 gene is normally expressed during embryogenesis (30,39,51) and in adult stem cells (46,49,52), but silenced postnatally in most differentiated cells. Through alternatively spliced mRNA, HMGA1 encodes HMGA1a and HMGA1b isoforms, which bind to AT-rich sequences, bend chromatin, and recruit transcriptional complexes to modulate gene expression (31-35, 37, 39, 42, 45-47, 49, 53).…”
Section: Resultsmentioning
confidence: 99%
“…Although GATA2 mutational analyses revealed loss-of-function phenotypes that may underlie pathogenesis ( 30 ), GATA2 variants can partially retain or have supraphysiological activity ( 33 , 34 ). GATA2 dysregulation is also implicated in myeloproliferative neoplasms ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to their regulatory roles, CRs are generally classified into three categories: histone modifications, chromatin remodelers, and DNA methylation [11,12]. Aberrant expression of CRs is associated with various biological processes such as apoptosis, autophagy, and proliferation, suggesting that dysregulation of CRs may contribute to the development of multiple diseases, including cancer [13][14][15]. Therefore, CRs are expected to become new targets for treating multiple diseases.…”
Section: Introductionmentioning
confidence: 99%